Projecting the potential distribution of Setaria palmifolia in China in response to climate change - Xiang, Yangzhou; Li, Suhang; Liu, Ying; Yang, Qiong; Zhang, Jinxin; Yao, Bin; Li, Yuan (Elsevier, 2026)
Accurately predicting the potential distribution of Setaria palmifolia in China is crucial for assessing its climatic adaptability as a forage resource and for developing sustainable utilization strategies. This study systematically integrated 927 species distribution records while employing a comprehensive set of multidimensional environmental variables, including climate, topography, vegetation, and human activity. Using an optimized Maximum Entropy (MaxEnt) model, we simulated the potential geographic distribution of S. palmifolia under both current conditions and future scenarios (2050s, 2070s, 2090s) across three Shared Socioeconomic Pathways (SSP126, SSP370, SSP585). The results identified the key environmental factors influencing its distribution: precipitation of the warmest quarter, precipitation of the coldest quarter, and temperature diurnal range. These factors collectively contributed 93.4% to the model. Under current climatic conditions, the total potentially suitable habitat for S. palmifolia is approximately 177.22 × 104 km2, primarily concentrated in southern China. Future projections indicate that the total suitable area will remain relatively stable across all scenarios (ranging from 177.22 × 104 to 196.80 × 104 km2). However, its internal structure will undergo significant reorganization, with highly suitable habitat expanding from 12.20 × 104 km2 (current) to between 29.69 × 104 and 50.39 × 104 km2 depending on emission scenarios. By the 2070s, this expansion is projected to reach 35.80 × 104 to 50.39 × 104 km2. Meanwhile, the distribution centroid shows complex, non-linear migration trajectories. This internal suitability reorganization pattern suggests that S. palmifolia responds to climate change through local adaptation rather than simple range shifts. Our findings provide critical scientific evidence and spatial decision-support for regional introduction planning, priority conservation area identification, and climate change adaptive management of S. palmifolia as a forage resource.
Keywords: Setaria palmifolia; MaxEnt model; climate change; model optimization; introduction planning